Effect of Different Urea Doses on the Performance of Wheat Under the Agro-Climatic Conditions of Mansehra, Khyber Pakhtunkhwa, Pakistan - Ali, Hazib; Fatima, Eman; Kumbhar, Abdul Qadir; Mujahid, Hamdia; Faisal, Muhammad; Fareed, Saima; Faridoon, Sara; Ahmad, Shumaila; Mehmood Ul Hassan; Iqbal, Arshad (Indus Journal of Bioscience Research, 2024)
The research conducted aimed to evaluate the impact of varying urea doses on the performance of wheat (Triticum aestivum), with a focus on growth, yield, and nitrogen use efficiency. Urea, a common nitrogen fertilizer, is crucial in enhancing crop productivity. The experiment was conducted in 2022-2023 at the Agriculture Research Station Baffa Mansehra in Khyber Pakhtunkhwa, Pakistan. The research material consisted of a Wheat variety. The Seeds were sown in RCBD design on 15th October 2022 at an Agriculture Research Station Baffa Mansehra. The experiment used a randomized complete block design with three replications. In the agro-climatic conditions of Mansehra, comprehensive data were gathered on various morphological and yield-related attributes. These included morphological parameters such as days to heading, leaf area index (cm), days to maturity, number of tillers/ plant-1, plant height (cm), spike length (cm), spikelet /spike, thousand-grain weight (g), grain yield kg/ha-1, and biological yield kg/ha-1. The study concludes that from experiments that wheat on different urea applications gives significant results from germination to till harvesting under the agro-climatic condition of Mansehra. It means that the wheat on different Urea applications shows improvement in Plant height, Spike length, Spikelet /spike, 1000-grain weight, grain yield and biological yield. Based on these results, it is recommended to apply urea at optimal rates to enhance wheat growth and yield, with the most effective rate being 65 grams per 6 m².